2018
DOI: 10.1016/j.oraloncology.2018.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Primary surgery for human papillomavirus-associated oropharyngeal cancer: Survival outcomes with or without adjuvant treatment

Abstract: Objectives Human papillomavirus-associated (HPV + ) oropharyngeal squamous cell carcinoma (OPSCC) is a unique form of head and neck cancer with improved prognosis. We assessed survival for stage I patients with low- or intermediate-risk pathologic features with surgery alone compared with surgery with adjuvant radiation (RT) or chemoradiation (CRT). Materials and methods We identified patients with stage I HPV+ OPSCC (after restaging with 8th edition staging system) treated with surgery alone, adjuvant RT or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
3
26
1
Order By: Relevance
“…Current studies examining survival in OPSCC have been largely limited to retrospective review. Consistent with previous reports, our prospectively-collected study showed 3-year overall survival for patients undergoing TORS at 93.2% (p=0.02) (28,29). Recent AJCC staging recommendations suggest 3-year survival being an adequate measure of cure in this disease(16).…”
Section: Discussionsupporting
confidence: 88%
“…Current studies examining survival in OPSCC have been largely limited to retrospective review. Consistent with previous reports, our prospectively-collected study showed 3-year overall survival for patients undergoing TORS at 93.2% (p=0.02) (28,29). Recent AJCC staging recommendations suggest 3-year survival being an adequate measure of cure in this disease(16).…”
Section: Discussionsupporting
confidence: 88%
“…The association of LVI with poorer survival for the S + CRT group may warrant additional attention. Prior NCDB studies of HPV-related OPSCC did not find an association between LVI and poorer survival in low-risk/surgery-alone cohorts, 30,31 which are distinct from the S + CRT cohort of this study. Studies with larger HPV-related OPSCC NCDB cohorts did not examine LVI as a risk factor.…”
Section: Discussioncontrasting
confidence: 65%
“…Both facility factors yielded a P value less than .2. On multivariable regression, patients with LVI were 1.6 times as likely to have [26][27][28][29][30][31][32][33][34][35].93], P < .001). When T4a and T4b were grouped into a single category on multivariable regression, T classification remained a significant predictor of margin status (for T4, OR: 6.94, CI: 3.14-15.30, P < .001), and the rest of the model was unchanged.…”
Section: Factors Associated With Positive Margins On Multivariable mentioning
confidence: 99%